Studi Inhibisi Korosi Pipa Sistem Pendingin Sekunder RSG-GAS BATAN Oleh Karboksimetil Kitosan - Edwin Rizki Safitra; Dwi Cahyani; Idra Herlina (Journal of Science and Applicative Technology, 2022)
Corrosion is one of the unavoidable problems in nuclear reactor cooling systems that use water as a cooling medium. secondary cooling systemThe Reaktor Serba Guna–G.A. Siwabessy (RSG-GAS) is an open recirculation cooling system that uses carbon steel pipes for water delivery. Due to the obvious open recirculation cooling system, components in the system interact with oxygen in the air, resulting in corrosion. Corrosion control in the RSG-GAS has been accomplished through the continuous injection of zinc phosphate (ZnPO4) inorganic inhibitors, but the use of these inhibitors can contribute to environmental pollution and health issues. To resolve these concerns, environmentally-friendly corrosion inhibitors such as carboxymethyl chitosan have been used. CMC (carboxymethyl chitosan) is widely used because it is more amphiprotic than other chitosan derivatives. Because of the number of functional groups in carboxymethyl chitosan, it is an effective corrosion inhibitor. The corrosion inhibition test by CMC on carbon steel in the secondary cooling water system was performed using a weight-loss method in this study with variations of 0, 1, and 3 g CMC. The steel material's composition is 0.23% C, 0.17% Si, 0.008% P, 0.004% S, 0.012% Cr, and 0.037% Mn. According to the study, the corrosion rate generated at variations of 0, 1, and 3 g CMC is 8.237, 5,645, and 5,113 mpy, respectively. According to the data, the addition of CMC can reduce the weight loss of steel due to corrosion because CMC contains many amphiprotic groups that are adsorbed on the surface in half-full d Fe orbitals.